Quan sát hình thái cấu trúc đáy hồ bằng công nghệ Georadar - Giảng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2005)
Ground penetrating radar = Georadar (GPR) is a high-resolution near-surface geophysical method which employ radio waves, typically in the 1 to 1000 MHz frequency range to map structure and features buried in the ground (or in man-made structures). The results of GPR survey are often processed radar profiles with physical parameters of materials as permittivity, velocity, electrical conductivity, attenuation, etc. Radar method offers the highest resolution and rapidly provides continuous graphic format which permits rapid semi-quantitative interpretation for in-field analysis. Recently, the Pulse EKKO 100 Geological System from Sensors & Software Inc. was a successful application system instrument for mapping structural morphology of bottom of the lake and shallow geological structure bellow of lake’s bottom. The interfaces between water layer, bottom of lake and the layer of clay bellow of bottom are located by georadar data. Especially two layers of water in Hoan Kiem lake are determined by radagram. This result is important for quality assessment of Hoan Kiem water. The Reflex program is used for interpretation and location morphology of lake on mountain Moc Chau by 3D georadar model.